FAKTOR PERILAKU PENCARIAN INFORMASI SISWA DI PERPUSTAKAAN SD NEGERI 34 PONTIANAK KOTA - Niarti, Intan; Hanum, Atiqa Nur Latifa; Rahman, Miftah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Student information search behavior is how to find information through the media and some get information from the school library. The purpose of this study was conducted to find out how internal factors and external factors that influence the search behavior of information on students of SD Negeri 34 Pontianak City. This study uses a descriptive method with a qualitative approach. The data collection method of this study uses observations, interviews, and documentary techniques. Data analysis techniques use data reduction, data presentation, and conclusions. Data validity techniques use credibility tests, increase perseverance, and triangulation. The results of the study showed that the internal factor that most influences information search is a person's psychological condition, because searching for information does not necessarily depend on mood because information is very important for everyday life. The second internal factor is the demographic factor, because it requires adequate facilities so that information can be obtained easily. The external factor that most influences information search is the environment, where the role of the school is very supportive of students in finding the information they want and the school also provides facilities such as libraries to support students in finding the information they need.